2022
DOI: 10.1002/art.42321
|View full text |Cite
|
Sign up to set email alerts
|

Syk Activation in Circulating and Tissue Innate Immune Cells in Antineutrophil Cytoplasmic Antibody–Associated Vasculitis

Abstract: Objective Syk is a cytoplasmic protein tyrosine kinase that plays a role in signaling via B cell and Fc receptors (FcR). FcR engagement and signaling via Syk is thought to be important in antineutrophil cytoplasm antibody (ANCA) IgG–mediated neutrophil activation. This study was undertaken to investigate the role of Syk in ANCA‐induced myeloid cell activation and vasculitis pathogenesis. Methods Phosphorylation of Syk in myeloid cells from healthy controls and ANCA‐associated vasculitis (AAV) patients was anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…In contrast, Mulder et al demonstrated that FcγRII was critically implicated in ANCA-induced neutrophil activation [ 8 ]. Although there remains a controversy about the pathways, Prendecki et al recently demonstrated that a signal transducer Syk, which acts downstream of FcγRs, was activated in patients with AAV [ 24 ]. These findings suggested that ANCA-induced FcγR-mediated signals are critical for neutrophil activation in AAV pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Mulder et al demonstrated that FcγRII was critically implicated in ANCA-induced neutrophil activation [ 8 ]. Although there remains a controversy about the pathways, Prendecki et al recently demonstrated that a signal transducer Syk, which acts downstream of FcγRs, was activated in patients with AAV [ 24 ]. These findings suggested that ANCA-induced FcγR-mediated signals are critical for neutrophil activation in AAV pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, ANCA immunoglobulin G could phosphorylate SYK at Y348. Accordingly, SYK inhibition could inhibit ANCA-mediated PLCγ/Vav/Ras/mitogen-activated protein kinases/NF-κB signaling [ 124 , 125 ]. Collectively, SYK is involved in the HF process by inducing myocardial fibrosis via activation of the TGF-β1/Smad3 pathway in cardiac tissues and modulating immune responses.…”
Section: Syk In Heart Failurementioning
confidence: 99%
“…Syk phosphorylation in neutrophils is increased in patients with active AAV, and is correlated with ANCA titers. Syk inhibition prevents the production of IL-8 and ROS by neutrophils in vitro ( 62 ). The treatment of fostamatinib, Syk inhibitor, is protective in AAV model rats induced by immunization with human MPO with the improvement of organ injury and and renal dysfunction ( 63 ).…”
Section: Targeting Nets Signaling Pathway In Aavmentioning
confidence: 99%